Gender Differences in Semantic Fluency Patterns in Children - Soriano, Federico; Fumagalli, Julieta; Shalom, Diego; Juan Pablo Barreyro; Macarena Martínez-Cuitiño (East European Journal of Psycholinguistics, 2016)
Previous literature in cognitive psychology has provided data involving differences in language processing between men and women. It has been found that women are usually more proficient with certain semantic categories such as fruit, vegetables and furniture. Men are reported to be better at other categories semantic, e.g. tools and transport. The aim of this article is to provide an inquiry about possible differences in semantic category processing of living things (LT) and inanimate objects (IO) by Argentinian Spanish-speakers school-aged children. The group of 86 children between 8 and 12 years old (51.16% boys) has been assessed on a semantic fluency task. Six semantic categories have been tested, three of them from the LT domain (animals, fruit/vegetables, and body parts) and three from the IO domain (transport, clothes and musical instruments). Results showed differences in semantic processing between boys and girls. Girls retrieved more items from the LT domain and activated more animals and fruit/vegetables. These findings appear to support an innate conceptual organization of the mind, which is presumably influenced by cultural factors and/or schooling. References Albanese, E., Capitani, E., Barbarotto, R., & Laiacona, M. (2000). Semantic category dissociations, familiarity and gender. Cortex, 36, 733–746. Barbarotto, R., Laiacona, M., & Capitani, E. (2008). Does sex influence the age of acquisition of common names? A contrast of different semantic categories. Cortex, 44(9), 1161–1170. doi: http://dx.doi.org/10.1016/j.cortex.2007.08.016 Capitani, E., Laiacona, M., & Barbarotto, R. (1999). Gender affects Word retrieval of certain categories in semantic fluency tasks. Cortex, 35, 273–278. doi: http://dx.doi.org/10.1016/S0010-9452(08)70800-1 Capitani, E., Laiacona, M., Mahon, B. Z., & Caramazza, A. (2003). What are the facts of semantic category-specific deficits? A critical review of the clinical evidence. Cognitive Neuropsychology, 20, 213–261. doi: http://dx.doi.org/10.1080/02643290244000266 Caramazza, A., & Mahon, B. Z. (2003). The organization of conceptual knowledge: The evidence from category-specific semantic deficits. Trends in Cognitive Sciences, 7, 354–361. Caramazza, A., & Mahon, B. Z. (2006). The organisation of conceptual knowledge in the brain: the future’s past and some future directions. Cognitive Neuropsychology, 23, 13–38 Caramazza, A., & Shelton, J. R. (1998). Domain-specific knowledge systems in the brain: The animate-inanimate distinction Journal of Cognitive Neuroscience, 10, 1–34. doi: http://dx.doi.org/10.1162/089892998563752 Casals-Coll, M., Sánchez-Benavides, G., Quintana, M., Manero, R. M., Rognoni, T., Calvo, L., & Peña-Casanova, J. (2013). Estudios normativos españoles en población adulta joven (proyecto NEURONORMA jóvenes): normas para los test de fluencia verbal. Neurología, 28(1), 33–40. Fumagalli, J.; Sorinano, F.; Shalom, D.; Barreyro, J.P; Martinez Cuitiño, M.M (In press). Phonological and semantic verbal fluency task in a sample of Argentinean children. Temas em Psychologia, 25(3). Gainotti, G. (2005). The influence of gender and lesion location on naming disorders for animals, plants and artefacts. Neuropsychologia, 43, 1633–1644. doi: http://dx.doi.org/10.1016/j.neuropsychologia.2005.01.016 Gainotti, G., Ciaraffa, F., Silveri, M. C., & Marra, C. (2010). Different views about the nature of gender-related asymmetries in task based on biological or artefact categories. Behavioural Neurology, 22(3–4), 81–90. doi: http://dx.doi.org/10.1155/2010/410858 Gainotti, G., Spinelli, P., Scaricamazza, E., & Marra, C. (2012). Asymmetries in genderrelated familiarity with different semantic categories. Data from normal adults. Behavioural Neurology, 27(2), 175–181. doi: http://dx.doi.org/10.1155/2013/138646 Gerlach, C., & Gainotti, G. (2016). Gender differences in category-specificity do not reflect innate dispositions. Cortex 85, 46–53.doi: http://dx.doi.org/10.1016/j.cortex.2016.09.022 Hurks, P., Vles, J., Hendriksen, J., Kalff, A., Feron, F., Kroes, M., . . . Jolles, J. (2006). Category Fluency Versus Initial Letter Fluency Over 60 Seconds as a Measure of Automatic and Controlled Processing in Healthy School-aged Children. Journal of Clinical and Experimental Neuropsychology, 28, 284–295. doi: 10.1080/13803390590954191 John, S., & Rajashekhar, B. (2014). Word retrieval ability on fluency task in typically developing Malayalam-speaking children. Child Neuropsychology: A Journal on Normal and Abnormal Development in Childhood and Adolescence, 20(2), 182–195. doi: http://dx.doi.org/10.1080/09297049.2012.760538 Koren, R., Kofman, O., & Berger, A. (2005). Analysis of word clustering in verbal fluency of school-aged children. Archives of Clinical Neuropsychology, 20, 1087–1104. doi: http://dx.doi.org/10.1016/j.acn.2005.06.012 Laiacona, M., Barbarotto, R., & Capitani, E. (2006). Human evolution and the brain representation of semantic knowledge: Is there a role for sex differences? Evol. Hum. Behav, 27, 158-168. doi: http://dx.doi.org/10.1016/j.evolhumbehav.2005.08.002 Laws, K. R. (1999). Gender afects latencies for naming living and nonliving things: implications for familiarity. Cortex, 35, 729–733. Laws, K. R. (2000). Category-specificity naming errors in normal subjects: the influence of evolution and experience. Brain and Language, 75, 123–133. doi: http://dx.doi.org/10.1006/brln.2000.2348 Laws, K. R. (2004). Sex differences in lexical size across semantic categories. Personality and invidual differences, 36, 23–32. doi: http://dx.doi.org/10.1016/S0191-8869(03)00048-5 Leite, G., Pires, I., Aragão, L., Lemos, P., Gomes, E., Garcia, D., Barros, P., Alencar, J., Fichman, H. & Oliveira, R. (2016). Performance of Children in Phonemic and Semantic Verbal Fluency Tasks. Psico-USF, 21(2), 293–304. https://dx.doi.org/10.1590/1413- 82712016210207 Lozano Guitiérrez, A., & Ostrosky-Solís, F. (2006). Efecto de la edad y la escolaridad en la fluidez verbal semántica: datos normativos en población hispanohablante. Revista Mexicana de Psicología, 23(1), 37–44. Mahon, B. Z., & Caramazza, A. (2003). Constraining questions about the organization and representation of conceptual knowledge. Cognitive Neuropsychology, 20, 433–450. Marino, J., Acosta Mesas, A., & Zorza, J. (2011). Control ejecutivo y fluidez verbal en población infantil: medidas cuantitativas,cualitativas y temporales. Interdisciplinaria, 28(2), 245–260. Marino, J., & Díaz-Fajreldines, H. (2011). Pruebas de fluidez verbal categoriales, fonológicas y gramaticales en la infancia: factores ejecutivos y semánticos. Revista Chilena de Neuropsicología, 6(1), 49–56. Marra, C., Ferraccioli, M., & Gainotti, G. (2007). Gender-Related Dissociations of Categorical Fluency in Normal Subjects and in Subjects With Alzheimer’s Disease. Neuropsychology, 21(2), 207–211. doi: http://dx.doi.org/10.1037/0894-4105.21.2.207 Martínez-Cuitiño, M.; Shalóm, D.; Borovinsky, G.; Szenkman, D. & Fumagalli, J. (2014) ¿Diferencias en el procesamiento semántico en niños en edad escolar? (77). Memorias del VI Congreso Internacional de Investigación y Práctica Profesional en Psicología, XXI Jornadas de Investigación, décimo encuentro de investigadores en Psicología del Mercosur. Adicciones: Desafíos y perspectivas para la investigación. McKenna, P., & Parry, R. (1994). Category-specificity in the naming of natural and man-made objects. Neuropsychological Rehabilitation, 4, 255–281. doi: 10.1080/09602019408401461 Moreno-Martínez, F. J., & Montoro, P. R. (2008). The impact of dementia , age and sex on category fluency: Greater deficits in women with Alzheimer’s disease. Cortex, 44,1256–1264. Moreno-Martínez, F. J. & Moratilla-Pérez, I. (2016). Naming and Categorization in Healthy Participants: Crowded Domains and Blurred Effects of Gender. The Spanish Journal of Psychology 19, 49, 1–15. doi:10.1017/sjp.2016.59 Nieto, A., Galtier, I., Barroso, J., & Espinosa, G. (2008). Fluencia verbal en niños españoles en edad escolar: estudio normativo piloto y análisis de las estrategias organizativas. Revista de Neurología, 46(1), 2–6. Olabarrieta Landa, L., Benito Sanchez, I., Landa Torre, E., López Mugartza Iriarte, J., Alegret, M., Arango-Lasprilla, J. (2015) The Effect of Specific Language on Performance on Verbal Fluency Tasks in Basque-Spanish Bilinguals. Arch Clin Neuropsychol, 30(6), 565. doi:10.1093/arclin/acv047.208 Pekkala, S., Goral, M., Hyun, J., Obler, L. K., Erkinjuntti, T., & & Albert, M. (2009). Semantic verbal fluency in two contrasting languages. Clin Linguist Phon., 23(6), 431–445. doihttp://dx.doi.org/10.1080/02699200902839800 Riva, D., Nichelli, F., & Devoti, M. (2000). Developmental Aspects of Verbal Fluency Confrontation Naming in Children. Brain and Language, 71, 267–284. doi: http://dx.doi.org/10.1006/brln.1999.2166 Soriano, F., Fumagalli, J., Shalóm, D., Carden, J., Borovinsky, G., Manes, F., & MartínezCuitiño, M. (2015). Sex differences in a semantic fluency task. East European Journal of Psycholinguistics, 2(1), 134–140. Spreen, O., & Strauss, E. A. (1998). Compendium of neuropsychological tests (2nd ed.). New York, NY: Oxford Univesity Press. Tulving, E. (1972). Episodic and semantic memory. In E. Tulving & W. Donaldson (Eds.), Organization Memory. New York: Academic Press.